LANGUAGE BY GENDER IN AUDIOVISUAL ON BRIDGERTON SERIES - Angelia, Ni Putu Putri; Pratama, Agus Darma Yoga (IJOLTL (Indonesian Journal of Language Teaching and Linguistics), 2023)
This research aimed to find out women’s language features that used by female characters in Bridgerton series and how expressions affect in women language. This research used Lakoff’s theory (1975) on women’s language features and Baker’s theory (2001) on semiotic channels. This research was using descriptive qualitative method and used note-taking as a technique to find the data. There were nine out of ten types of women language features used by female characters in Bridgerton Series. From ten women’s language features mentioned by Lakoff (1975), only nine women's language features appeared in Bridgerton series. Based on the research, lexical hedges or filler became the dominant type of women’s language features uttered in this drama, From ten women’s language features mentioned by Lakoff (1975), only nine women's language features appeared in Bridgerton series. They are lexical hedges or fillers (34), tag question (4), rising intonation on declaratives (16), empty adjectives (11), intensifiers (5), hypercorrect grammar (4), super polite forms (7), avoid to use strong or swear words (9), and emphatic stress (7). The lexical hedges or fillers feature is most often used by the female characters in this drama, because they need time to express their feelings so that the conversation keep going.